A Literature Review On The Use Of Songs In Teaching English To Young Learners: Benefits And Difficulties - Widya Febrina (PT. Padang Tekno Corp, 2023)
This paper contains a comprehensive literature review on the use of songs in teaching English to young learners. This paper reviews the concept of teaching English to young learners, and then discusses the benefits and difficulties in using songs and how songs should be implemented in English as a Foreign Language (EFL) classroom. A number of previous studies from 2008 to 2015 investigating the use of songs in teaching English have been analysed. Most of the studies used in this research are empirical studies. It is found that the benefits of songs to teach English can be classified into four categories: (1) affective; (2) cognitive; (3) linguistic; and (4) culture. This review presents a better understanding on the benefits and difficulties of using songs to teach English to young learners. It can be argued that teaching English songs to young learners is prominent. At the end, the author outlines several recommendations regarding on how to overcome the difficulties in teaching songs so the use of songs in teaching can be maximised.